Overview Of Criminology And Criminal Law Concerning The Criminal Act Of Abuse Performed By Parents Against This Bird Children (Study Of The Decision Of The State Court Tulung Agung Number 179/Pid.Sus/2012/PN. Ta) - Maya Etrisna Mendrofa (Journal of Law Science, 2022)
The Indonesian nation is known as a nation that loves children. Turns out this is just a myth. Many cases of physical violence or cases of child abuse in their own families are not taken seriously by law enforcement. This situation causes the dark number to be high because it is not reported. Though the impact of the perpetrator tends to damage the mental even the victim is mentally retarded. This is certainly the main idea and responsibility of the government and society as observers of the nation's children who are the next generation of the nation's ideals. Why abuse among children is increasing, how does our positive law issue policies to deal with cases of violence experienced by children, and what other efforts can be taken to overcome violence experienced by children into the formulation of the problem of this thesis. The approach method used in this research is normative juridical, which is a deductive research that begins with an analysis of the articles in the laws and regulations governing thesis problems. Normative nature means legal research that aims to obtain normative knowledge about the relationship between one regulation and another and its application in practice (decision study). The factors that cause the occurrence of criminal acts of abuse or violence against children by their own parents are classified into two parts, namely internal factors and external factors. In dealing with cases of abuse experienced by children, it consists of criminal law policies such as the application of criminal sanctions and the application of legal protection for children. In addition, in tackling the crime of child abuse, there are several efforts that can be taken, namely preventive efforts, repressive efforts and reformative efforts.